Implementasi Algoritma Simple Additive Weighting Berbasis Web Untuk Penentuan Calon Penerima Beasiswa - Elfri Kartini Hutabarat; Mugiarso; Rafika Sari; Rasim (Journal of Informatic and Information Security, 2024)
Technology aids humans in performing activities such as accessing information in all fields, particularly in education. One implementation adopted by educational institutions is the student information system. As an educational institution, SMK Yadika 13 Tambun runs a scholarship program. The school's selection process is still manual, conducted through document requirements. Consequently, the selection process takes a long time due to the high number of applicants. Only those meeting the criteria receive scholarships. The large number of applicants and the limited scholarship quota make it challenging for the school to manually screen documents. The research objective is to determine prospective scholarship recipients at SMK Yadika 13 Tambun and implement the Simple Additive Weighting method in a decision support system that can provide alternatives in determining scholarship recipients. The Simple Additive Weighting algorithm can be applied in determining scholarship recipients. This algorithm can serve as an exemplary calculation method as it can identify alternatives for each attribute. Subsequently, a ranking system is devised to select the best alternatives. The system developed can assist SMK Yadika 13 Tambun Bekasi in determining scholarship recipients more efficiently and systematically, thereby reducing errors in the selection process.